2022
DOI: 10.1002/eat.23762
|View full text |Cite
|
Sign up to set email alerts
|

Attachment insecurity predicts worse outcome in patients with eating disorders treated with enhanced cognitive behavior therapy: A one‐year follow‐up study

Abstract: Objective: This study aimed to explore the role of attachment insecurity in predicting a worse longitudinal trend of eating disorder (ED) psychopathology and body uneasiness in patients with Anorexia Nervosa (AN) or Bulimia Nervosa (BN) treated with Enhanced Cognitive Behavior Therapy, considering the longitudinal interplay between these dimensions. Method: In total, 185 patients with AN or BN performed the baseline assessment, and 123 were re-evaluated after 1 year of treatment. Participants completed questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Preliminary data suggest that EABT may have utility for a subset of adults with AN (Wildes et al., 2014). Moreover, the evidence of a worse longitudinal trend of ED psychopathology in individuals with EDs and insecure attachment treated with CBT‐E (Rossi et al., 2022) could be explained considering that CBT‐E does not address attachment issues as specific targets of intervention. A recent longitudinal study demonstrated that emotion dysregulation was the nexus linking early traumatic experiences and worse response to CBT‐E in patients with AN (Cassioli et al., 2022), suggesting that persistence of difficulties in emotion regulation might maintain ED psychopathology in insecurely attached patients treated with CBT‐E (Cortés‐García et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data suggest that EABT may have utility for a subset of adults with AN (Wildes et al., 2014). Moreover, the evidence of a worse longitudinal trend of ED psychopathology in individuals with EDs and insecure attachment treated with CBT‐E (Rossi et al., 2022) could be explained considering that CBT‐E does not address attachment issues as specific targets of intervention. A recent longitudinal study demonstrated that emotion dysregulation was the nexus linking early traumatic experiences and worse response to CBT‐E in patients with AN (Cassioli et al., 2022), suggesting that persistence of difficulties in emotion regulation might maintain ED psychopathology in insecurely attached patients treated with CBT‐E (Cortés‐García et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that secure attachment predicts positive alliance in eating disorder treatment (Folke et al, 2016; Jewell et al, 2021). There have been few adequately‐powered studies of attachment as a predictor of outcome in eating disorders: Jewell et al (2021) reported null findings in relation to family therapy for adolescent AN, but Rossi et al (2022) and Illing et al (2010) both found attachment insecurity to predict higher ED psychopathology in adults with AN and BN receiving cognitive behavior therapy and day‐hospital group therapy, respectively. Finally, attachment could be relevant to eating disorder recovery, even in the absence of psychological treatment, since social connection to close others is a consistent theme in qualitative studies of recovery (Bardone‐Cone et al, 2018; Bohrer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence showed that treatment response is far from satisfactory, as remission rates are about 50% (Atwood & Friedman, 2020), with a consequent risk of chronicity, disability, and mortality (Steinhausen, 2009; Fichter & Quadflieg, 2016; van et al., 2020). Thus, scholars are investigating reasons for lack of response, including psychopathological features not adequately challenged by CBT‐E, and possibly linked to different developmental trajectories (Cassioli, Rossi, D’Anna, et al., 2022; Halmi, 2013; Longo et al., 2023; Rossi et al., 2022).…”
Section: Introduction and Aimsmentioning
confidence: 99%